2016
DOI: 10.1016/j.jid.2016.05.116
|View full text |Cite
|
Sign up to set email alerts
|

CD271 Down-Regulation Promotes Melanoma Progression and Invasion in Three-Dimensional Models and in Zebrafish

Abstract: CD271 is a neurotrophin receptor variably expressed in melanoma. Although contradictory data are reported on its role as a marker of tumor-initiating cells, little is known about its function in tumor progression. CD271 expression was higher in spheroids derived from freshly isolated cells of primary melanomas and in primary WM115 and WM793-B cell lines, and it decreased during progression to advanced stages in cells isolated from metastatic melanomas and in metastatic WM266-4 and 1205Lu cell lines. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 32 publications
2
35
0
Order By: Relevance
“…The low levels of β 1 integrin and the decreased of cell-to-cell adhesion in the absence of p75 NTR could predispose melanoma to increased invasiveness (93). Furthermore, melanoma is characterized by an alteration of the apoptotic machinery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low levels of β 1 integrin and the decreased of cell-to-cell adhesion in the absence of p75 NTR could predispose melanoma to increased invasiveness (93). Furthermore, melanoma is characterized by an alteration of the apoptotic machinery.…”
Section: Resultsmentioning
confidence: 99%
“…To definitely assess the role of p75 NTR in melanoma, we have recently carried out an extensive study in vitro and in vivo (93). In skin equivalent models, p75 NTR is highly expressed in early melanomas at the epidermal level and tends to disappear when melanoma starts to invade the dermis.…”
Section: P75ntr and Melanoma: More Than Just A Markermentioning
confidence: 99%
“…We previously demonstrated that in melanoma MCTS, the expression level of several melanoma markers (CD271, HIF‐1α, ABCB5 and Oct4) observed in skin lesion and freshly isolated cells are maintained in spheroids derived from the same patients up to 168 hours …”
Section: Melanoma 3d Modelsmentioning
confidence: 99%
“…Figure shows an example of this assay performed using five melanoma cell lines of different origin. To quantify the invasive ability, it is possible to measure the spheroids area and the invasion area in pixel by ImageJ software, the factor shape, the percentage of fragmentation and the distance reached by cells, as reported in several studies . It should be also noted that the presence of stromal cells would better recapitulate the tumor microenvironment.…”
Section: Melanoma 3d Modelsmentioning
confidence: 99%
“…Moreover, OCT4 expression in melanoma cells was induced by hypoxia and its expression was detected in a sub-population of melanoma cells from clinical samples [141] . Overexpressing CD271 on human melanoma cell lines was shown to reduce their invasive and metastatic traits, whereas CD271melanoma cells showed less adhesive, more highly proliferative and invasive traits in vitro and in vivo [142] . Mechanistically, similar to EPCAM, it was found that the CD271 ICD regulated proliferation [143] .…”
Section: Cd271 (P75ntr)mentioning
confidence: 97%